Memorandum of Understanding between the Colgate University, New York, USA and BRAC University, Dhaka, Bangladesh (2011) - Colgate University; BRAC University (Colgate University and BRAC University, 2013)
1. Purpose. 2. General Considerations. 3. Responsibilities of BRAC University. 4. Responsibilities of Colgate University.